2021
DOI: 10.1038/s41598-021-81399-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic profiling of the effective ingredients and mechanism of Scabiosa comosa and S. tschilliensis against hepatic fibrosis combined with network pharmacology

Abstract: Scabiosa comosa and S. tschilliensis (SCST) are traditionally used for liver diseases in Mongolian medicine. However, their active ingredients and molecular mechanisms are unknown. The present study employed network pharmacology and experimental verification approaches to decipher the common pharmacological mechanisms of SCST on liver fibrosis, which is the key step in liver diseases. We predicted the targets of all available SCST ingredients with the SWISS and SuperPred servers and clustered the targets relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In accordance with previous studies, these results indicated that the above pathways had important effects on the progression and advancement of EMT. Among them, the Wnt/β-catenin pathway is the best researched anti-fibrosis pathway related to EMT ( ChenQ et al, 2021 ; Gao, et al, 2020 ). Therefore, the Wnt/β-catenin pathway may play a crucial role in JPYSF against EMT.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous studies, these results indicated that the above pathways had important effects on the progression and advancement of EMT. Among them, the Wnt/β-catenin pathway is the best researched anti-fibrosis pathway related to EMT ( ChenQ et al, 2021 ; Gao, et al, 2020 ). Therefore, the Wnt/β-catenin pathway may play a crucial role in JPYSF against EMT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using the interaction networks, Chen et al . [ 70 ] found that the main effective ingredients in Scabiosa comosa and Scabiosa tschilliensis for treating liver diseases are flavonoids which were experimentally validated. Based on the compound-target network of Cistanche tubulosa , the top ingredients with strong synergy potential for anti-inflammatory effect were predicted and validated by experiments in vitro [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preceding works of literature mainly stated medicinal application of Scabiosa is vastly contributed by its biologically active compounds such as iridoids, pentacyclic triterpenoids and polyphenolic compounds. These compounds were mostly found in this species of plants and yield beneficial therapeutic properties such as antioxidant, anti-fibrotic, anti-inflammatory, anti-HCV, anti-amnesic, antitumor and antibacterial activity 2,[4][5][6][7][8][9][10] . In the case of SC, the inflorescence of SC used along with Scabiosa tschilliensis, ʻLanpenhuaʼ in Chinese, was traditionally used to treat liver disease in Mongolian folk medicine 8 .…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were mostly found in this species of plants and yield beneficial therapeutic properties such as antioxidant, anti-fibrotic, anti-inflammatory, anti-HCV, anti-amnesic, antitumor and antibacterial activity 2,[4][5][6][7][8][9][10] . In the case of SC, the inflorescence of SC used along with Scabiosa tschilliensis, ʻLanpenhuaʼ in Chinese, was traditionally used to treat liver disease in Mongolian folk medicine 8 . Also, used as a remedy for headache, fever, cough, liver heat, pulmonary heat and throat heat 4 .…”
Section: Introductionmentioning
confidence: 99%